Notes About Persons and Places (Academy of Management Journal, 1966)
The article presents information about Academy of Management members. The 1966 Human Relations Award from the Society for the Advancement of Management was awarded to Keith Davis, professor of management at the Arizona State University. James H. Mullen was appointed vice-president for academic affairs at Rider College. Joseph V. Miccio, Eugene Richman and Mary Hopkins will join the management faculty of the College of Business Administration of the University of Hawaii.